Prevalence of zinc-rich food consumption and associated factors in children at a children's home in Pamplona, Colombia - Carvajal-Suárez, Lennys Soley; Espinel-Villamizar, Natalia Margarita; Rojas-Cárdenas, Melissa Sharick (Universidad y Salud, 2026)
Introduction: Zinc is an important mineral for the organism given its structural function and its importance in cell growth, therefore, a good intake of this mineral prevents infant mortality. Objective: to determine the prevalence of consumption of food sources of zinc and associated factors in children aged 1 to 4 years. Materials and methods: a descriptive observational study was carried out with an analytical, prospective, cross-sectional approach; a structured questionnaire was used for data collection, which was applied by personal interview. Results: The food groups with the highest prevalence of consumption were meats and meat products, cereals and cereal products, legumes, tubers, nuts and seeds; mean frequency/day was 1.1, mean/week between 1.2 to 5.0 and mean/month ranged from 1.8 to 6.6; the prevalence of zinc supplementation was 15.8%; statistically significant differences were found with some demographic and socioeconomic characteristics assessed. Conclusions: Factors such as sex, nationality, origin, marital status, socio-economic status, number of family members, income, money spent on food are related to the consumption of foods from the meat, cereals, fruits, vegetables, legumes and miscellaneous groups.